2004
DOI: 10.1007/bf03033300
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the mGluR5 gene with breeding and maternal factors on startle and prepulse inhibition in mice

Abstract: Sensorimotor gating, measured by prepulse inhibition (PPI), is a fundamental form of information processing that is deficient in schizophrenia patients and mice lacking the gene for metabotropic glutamate receptor 5 (mGluR5). Both breeding strategies and mothering behaviors are capable of influencing the behavioral phenotype of knockout (KO) mice. Previous studies found a PPI deficit and increased startle magnitudes in mGluR5 KO mice derived from homozygous matings. Here we compared the PPI of mGluR5 wildtype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 93 publications
0
18
0
Order By: Relevance
“…Given that different PPI protocols seem to confer differential Fmr1 KO responses, this may reflect varying molecular pathways underlying each protocol and therefore may be one reason why we did not observe a similar MPEP normalization of Fmr1 KO PPI behavior using our protocol. While the doses for MPEP used in this study fall within the range used by de Vrij, as well as a number of other groups reporting no effect of MPEP in mice or rats (Brody and Geyer 2004;Henry et al 2002;Hikichi et al 2010;Schulz et al 2001;Spooren et al 2000b;Zou et al 2007), we cannot discount the possibility that higher doses of JNJ might alter PPI responses considering a recent report suggesting that only high JNJ doses (3 and 10 mg/kg) alter PPI responses in mice (Hikichi et al 2010). The PPI phenotype we observe using the whole-body flinch is not only different from that reported in the de Vrij study, but it also does not reflect the same PPI deficit typically reported in FXS individuals (Frankland et al 2004); nevertheless, it represents a robust and consistent phenotype observed in multiple labs.…”
Section: Discussionmentioning
confidence: 73%
“…Given that different PPI protocols seem to confer differential Fmr1 KO responses, this may reflect varying molecular pathways underlying each protocol and therefore may be one reason why we did not observe a similar MPEP normalization of Fmr1 KO PPI behavior using our protocol. While the doses for MPEP used in this study fall within the range used by de Vrij, as well as a number of other groups reporting no effect of MPEP in mice or rats (Brody and Geyer 2004;Henry et al 2002;Hikichi et al 2010;Schulz et al 2001;Spooren et al 2000b;Zou et al 2007), we cannot discount the possibility that higher doses of JNJ might alter PPI responses considering a recent report suggesting that only high JNJ doses (3 and 10 mg/kg) alter PPI responses in mice (Hikichi et al 2010). The PPI phenotype we observe using the whole-body flinch is not only different from that reported in the de Vrij study, but it also does not reflect the same PPI deficit typically reported in FXS individuals (Frankland et al 2004); nevertheless, it represents a robust and consistent phenotype observed in multiple labs.…”
Section: Discussionmentioning
confidence: 73%
“…It has been reported that many neurological disorders such as Parkinson's disease (PD), Schizophrenia, mood disorders, drug addiction, and pain might be affected by the direct or indirect effects of mGluR5s. Metabotropic glutamate subtype-5 receptors have also been tested as potential neuroprotective drugs (Chiamulera et al, 2001;Marino et al, 2003;Sotgiu et al, 2003;Brody and Geyer, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, postnatal maternal factors influenced the ASR in mGluR5 KO mice derived from homozygous and heterozygous matings, although possible influences of the uterine environment were not studied (Brody and Geyer 2004). Other environmental postnatal factors also alter the amplitude of the ASR in the offspring.…”
Section: Uterine and Postnatal Effectsmentioning
confidence: 99%